The Analysis of Factors Influencing Employee Performance in Palm Oil Harvesting at PT. Semadam - Hanisah Hanisah; Mukti Hanjani; Supristiwendi Supristiwendi; Cut Gustiana; Rini Mastuti (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2023)
The palm oil industry has created business potential. Palm oil agribusiness is one of the industrial sectors in Indonesia that possesses a competitive advantage in the global market. The development of the palm oil industry in Indonesia has been carried out with a focus on achieving a balance among social, financial, and environmental aspects. The attention of oil palm plantation employees is crucial for increasing productivity. This research aims to analyze the influence of the harvest premium variables: length of service, age, education level, number of dependents, grants, and geology on the work implementation of oil palm harvesting workers at PT Semadam. This research was conducted in June 2022 at PT. Semadam, Aceh Tamiang. In this research, the survey method was employed. The number of samples was calculated using the Slovin Formula with an error rate of 10% or 0.1. This calculation obtained a sample size of 40 respondents from a population of 45 people. The research results indicate a collective influence of independent factors (premium collection, work involvement, age, education level, number of dependents, aid funds, and geographical location) on the dependent variable (work implementation). However, premium collection, education level, and geography significantly influence worker performance, while work involvement, age, work involvement, and grants do not substantially impact worker performance. The coefficient of determination, 0.825, indicates that the independent variables explain 82.5% of the variance in the dependent variable, while other factors influence 17.5%.